Extraction, isolation, synthesis, and biological evaluation of novel piperic acid derivatives for the treatment of Alzheimer’s disease - Kumar J.; Shankar G.; Kumar S.; Thomas J.; Singh N.; Srikrishna S.; Satija J.; Krishnamurthy S.; Modi G.; Mishra S.K. (My University, 2025)
In this paper, we developed a series of piperic acid (PA) analogs with the aim of overcoming the limitations associated with the natural products for the management of Alzheimer’s disease (AD). A comprehensive SAR study was performed to enhance cholinesterase inhibition of PA. The acetylcholinesterase inhibition and its kinetic data suggested 6j as the lead molecule (AChE IC50 = 2.13 ± 0.015 µM, BChE = 28.19 ± 0.20%), in comparison to PA (AChE = 7.14 ± 0.98%) which was further selected for various biological studies in AD models. 6j, exhibited interaction with the peripheral anionic site of AChE, BBB permeability (Pe = 7.98), and antioxidant property (% radical scavenging activity = 35.41 ± 1.09, 2.43 ± 1.65, for 6j and PA at 20 Mμ, respectively). The result from the metal chelation study suggests that 6j did not effectively chelate iron. The molecular modeling studies suggested that 6j could effectively interact with Ser293, Phe295, Arg296, and Tyr34 of AChE. In the cell-based cytotoxicity studies, 6j exhibited cytocompatibility at the different tested concentrations. The acute toxicity data on mice suggested that compound 6j had no renal and hepatotoxicity at 500 mg/kg. Moreover, 6j could effectively reverse scopolamine-induced amnesia by improving spatial and cognitive memory in mice. The above results strongly suggest that compound 6j may act as a novel multi-targeted lead for AD therapy. Graphical abstract: (Figure presented.) © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2023.